We have to expand: ln(3e^(2x)).

Here we make use of the relations log a^n = n* log a and log ab = log a + log b

ln(3e^(2x))

=> ln 3 + ln e^2x

=> ln 3 + 2x*ln e

ln e = 1

=> ln 3 + 2x

** The...**

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to expand: ln(3e^(2x)).

Here we make use of the relations log a^n = n* log a and log ab = log a + log b

ln(3e^(2x))

=> ln 3 + ln e^2x

=> ln 3 + 2x*ln e

ln e = 1

=> ln 3 + 2x

**The required expansion is ln 3 + 2x**